Active energy ray curable overprint varnish and paper or plastic substrate using same
Patent Information
- Application Number
- JP2021048409
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-23
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-03-23
AI Technical Summary
【0012】 本発明の活性エネルギー線硬化性オーバーコートニスは抗菌及び抗ウイルス性能を有するので、紙基材やフィルムにコーティングするのみで、紙基材又はプラスチック基材に抗菌性や抗ウイルス性を付与することができる。
Smart Images

Figure 0007633055000001 
Figure 0007633055000002 
Figure 0007633055000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable overprint varnish containing an active energy ray-curable compound as a main component. [Background technology]
[0002] For the purpose of improving the gloss of printed matter and protecting the film of printed matter, an overprint varnish (also called an overcoat varnish; hereafter sometimes referred to as OP varnish) is used after printing. Specifically, after printing each color of printing ink, a colorless and transparent OP varnish is printed. As for OP varnish, in addition to solvent-type OP varnishes that contain an organic solvent and form a varnish film when dried, active energy ray-curable OP varnishes are also known (see, for example, Patent Documents 1 and 2).
[0003] On the other hand, in recent years, there has been a demand for imparting functionality to the surfaces of various substrates, and there is a need to improve the surface properties of not only printed matter but also plastic materials, molded products, paper substrates, film substrates, packaging materials, etc. In recent years in particular, in addition to physical functionality such as improved gloss and film protection, hygienic functions such as antibacterial and antiviral properties are also desired, and there is an urgent need for antiviral (virus inactivation) measures as a countermeasure against viral infections, particularly those caused by new strains of influenza, SARS (Severe Acute Respiratory Syndrome), and norovirus.
[0004] As an OP varnish composition having antiviral properties, for example, an OP varnish composition characterized by containing polytetrafluoroethylene particles and an antibacterial agent in an OP varnish is known (see, for example, Patent Document 3). However, an active energy ray-curable OP varnish having antibacterial or antiviral properties has not been known until now. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-163293 A [Patent Document 2] Japanese Patent Application Publication No. 07-196948 [Patent Document 3] Japanese Patent Application Publication No. 11-80643 Summary of the Invention [Problem to be solved by the invention]
[0006] The problem to be solved by the present invention is to provide an active energy ray-curable overcoat varnish having antibacterial and antiviral properties. [Means for solving the problem]
[0007] The present inventors have solved the problem by providing an active energy ray-curable overprint varnish that contains a specific amount of a photocatalyst relative to the solid content of the varnish.
[0008] That is, the present invention provides an active energy ray-curable overprint varnish whose main component is an active energy ray-curable compound, the active energy ray-curable overprint varnish containing a photocatalyst, the photocatalyst containing titanium oxide including crystalline rutile-type titanium oxide and a divalent copper compound, the crystalline rutile-type titanium oxide being a titanium oxide having a full width at half maximum of 0.65 degrees or less of the strongest diffraction peak corresponding to rutile-type titanium oxide in an X-ray diffraction pattern obtained by plotting diffraction line intensity against diffraction angle 2θ using Cu-Kα radiation, the content of the crystalline rutile-type titanium oxide in the titanium oxide being 50 mol % or more and the content of anatase-type titanium oxide being less than 50 mol %, and the photocatalyst containing 0.01 to 15 mass % of the photocatalyst relative to the total solids content of the varnish.
[0009] The present invention also provides a printed matter comprising a substrate and a coating film of the active energy ray-curable overprint varnish according to any one of claims 1 to 3 disposed on the substrate.
[0010] The present invention also provides a paper substrate or a plastic substrate obtained by coating a paper substrate or a film with the above-described active energy ray-curable overprint varnish.
[0011] The present invention also provides containers and packaging materials using the paper substrate or plastic substrate. Effect of the Invention
[0012] Since the active energy ray-curable overcoat varnish of the present invention has antibacterial and antiviral properties, it is possible to impart antibacterial and antiviral properties to a paper substrate or a plastic substrate simply by coating the same on the paper substrate or a film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (Active energy ray curable overprint varnish) The active energy ray-curable overprint varnish used in the present invention contains, as a main component, an active energy ray-curable compound such as an active energy ray-curable monomer and / or oligomer.
[0014] (Monomers having ethylenically unsaturated double bonds) The active energy ray curable monomer and / or oligomer used in the present invention can be used without any particular limitation as long as it is a monomer and / or oligomer used in the active energy ray curable technical field. In particular, those having a (meth)acryloyl group, a vinyl ether group, etc. as a reactive group are preferred. There is also no particular limitation on the number of reactive groups or molecular weight, and those having a larger number of reactive groups tend to have higher reactivity but higher viscosity and crystallinity, and those having a higher molecular weight tend to have higher viscosity, so that they can be used in appropriate combination according to the desired physical properties. For example, in terms of suitable curing with low energy irradiation such as UV-LED, it is preferable to combine a more reactive trifunctional or higher active energy ray curable monomer, and to use monofunctional or bifunctional monomers alone or in combination as appropriate to obtain the necessary physical properties such as adhesion to printing substrates and flexibility of the film depending on the application.
[0015] Examples of monofunctional (meth)acrylates include ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, isoamyl (meth)acrylate, isodecyl (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, methoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenoxydiethylene glycol ( (meth)acrylate, nonylphenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, diethylaminoethyl (meth)acrylate, nonylphenoxyethyl tetrahydrofurfuryl (meth)acrylate, caprolactone-modified tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and the like.
[0016] Examples of the difunctional or higher functional (meth)acrylates include 1,4-butanediol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 2-methyl-1,8-octanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene Di(meth)acrylates of dihydric alcohols such as ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and di(meth)acrylates of tris(2-hydroxyethyl)isocyanurate, and di(meth)acrylates obtained by adding 4 or more moles of ethylene oxide or propylene oxide to 1 mole of neopentyl glycol Di(meth)acrylates of diols, di(meth)acrylates of diols obtained by adding 2 moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A, poly(meth)acrylates of trihydric or higher polyhydric alcohols such as trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and poly(meth)acrylate of dipentaerythritol. and poly(meth)acrylates of polyoxyalkylene polyols such as tri(meth)acrylates of triols obtained by adding 3 moles or more of ethylene oxide or propylene oxide to 1 mole of glycerin, di- or tri(meth)acrylates of triols obtained by adding 3 moles or more of ethylene oxide or propylene oxide to 1 mole of trimethylolpropane, and di(meth)acrylates of diols obtained by adding 4 moles or more of ethylene oxide or propylene oxide to 1 mole of bisphenol A.
[0017] Examples of the polymerizable oligomer include amine-modified polyether (meth)acrylates, amine-modified epoxy (meth)acrylates, amine-modified aliphatic acrylates, amine-modified polyester (meth)acrylates, amine-modified (meth)acrylates such as amino (meth)acrylates, thiol-modified polyester (meth)acrylates, thiol-modified (meth)acrylates such as thiol (meth)acrylates, polyester (meth)acrylates, polyether (meth)acrylates, polyolefin (meth)acrylates, polystyrene (meth)acrylates, epoxy (meth)acrylates, and urethane (meth)acrylates.
[0018] In addition, as the active energy ray curable monomer and / or oligomer, it is preferable to use tetrafunctional or higher (meth)acrylates in printing applications on paper such as fine paper, coated paper, art paper, imitation paper, thin paper, and thick paper, since they greatly contribute to improving curability and strength, and it is preferable to use them in the range of 15 to 70 mass% based on the total solid content of the varnish. On the other hand, in printing applications on plastics, as the crosslink density of the cured coating film increases, the adhesion between the substrate and the cured coating film decreases, so it is necessary to appropriately reduce the content of tetrafunctional or higher (meth)acrylates. In this case, it is preferable to use tetrafunctional or higher (meth)acrylates in the range of 0 to 50 mass% based on the total solid content of the ink.
[0019] In addition, resins, pigments, and various additives can be used in the active energy ray-curable overprint varnish of the present invention.
[0020] (resin) As the resin, various known and used binder resins can be used. The binder resin described here refers to any resin having appropriate pigment affinity and dispersibility and rheological properties required for printing inks. For example, non-reactive resins include diallyl phthalate resins, epoxy resins, epoxy ester resins, polyurethane resins, polyester resins, petroleum resins, rosin ester resins, poly(meth)acrylic acid esters, cellulose derivatives, vinyl chloride-vinyl acetate copolymers, polyamide resins, polyvinyl acetal resins, butadiene-acrylonitrile copolymers, etc., and epoxy (meth)acrylate compounds, urethane (meth)acrylate compounds, polyester (meth)acrylate compounds, etc. having at least one polymerizable group in the molecule can also be used. These binder resins may be used alone or in combination of one or more of them.
[0021] In the present invention, it is preferable to use polyester (meth)acrylate and diallyl phthalate resin in combination. The polyester (meth)acrylate is preferably a polyester (meth)acrylate having a glass transition temperature of 200° C. or higher. Of these, the polyester (meth)acrylate having a glass transition temperature of 250° C. or higher is more preferable. The content of polyester (meth)acrylate is preferably 5 to 40% by mass, and more preferably 10 to 35% by mass, based on the total amount of the active energy ray-curable overprint varnish.
[0022] The diallyl phthalate resin is preferably a diallyl phthalate resin having a glass transition temperature of 140° C. to 160° C., more preferably 150° C. to 160° C. Furthermore, it is preferably contained in an amount of 5 to 30% by mass based on the total amount of the active energy ray-curable overprint varnish.
[0023] In particular, it is preferable that the active energy ray-curable overprint varnish contains 10 to 35 mass % of polyester (meth)acrylate and 5 to 20 mass % of diallyl phthalate resin based on the total amount of the active energy ray-curable overprint varnish.
[0024] It is also preferable that the varnish contains both a polyester (meth)acrylate having a glass transition temperature of 250° C. or higher and a diallyl phthalate resin having a glass transition temperature of 140 to 160° C. In this case, the total mass of the polyester acrylate having a glass transition temperature of 250° C. or higher and the diallyl phthalate resin having a glass transition temperature of 140 to 160° C. is preferably 10 to 70% by mass based on the total amount of the active energy ray-curable overprint varnish.
[0025] (Photopolymerization initiator) The photopolymerization initiator used in the present invention is not particularly limited and may be any known photopolymerization initiator. For example, alkylphenone photopolymerization initiators such as 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone (184), 2-hydroxy-2-methyl-1-phenyl-propan-1-one (1173), 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one (2959), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one (127), and 2-hydroxy-1-[4-[4-(2-hydroxy-2-methylpropanoyl)phenoxy]phenyl]-2-methylpropan-1-one;
[0026] Phenyl glyoxylic acid methyl ester, oxyphenylacetic acid, mixture of 2-[2-oxo-2-phenylacetoxyethoxy]ethyl ester and oxyphenylacetic acid, 2-(2-hydroxyethoxy)ethyl ester, 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime), 2-methyl-1-(4-methylthiophenyl)-2-morpholino Examples of compounds that can be used include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-benzyl-2-dimethylamino-1-(4-piperidinophenyl)-butan-1-one, 1-([1,1'-biphenyl]-4-yl)-2-methyl-2-morpholinopropan-1-one, and 1-(4-methoxyphenyl)-2-methyl-2-(4-morpholinyl-1-propanone.
[0027] Further examples include acylphosphine oxide compounds such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and ethyl-(2,4,6-trimethylbenzoyl)phenylphosphineate.
[0028] Further examples of thioxanthone compounds include 2,4-diethylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diisopropylthioxanthone, 2-isopropylthioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-dichlorothioxanthone, 2-chlorothioxanthone, 1-chloro-4-propoxythioxanthone, and 2-hydroxy-3-(3,4-dimethyl-9-oxo-9H-thioxanthone-2-yloxy-N,N,N-trimethyl-1-propanamine hydrochloride.
[0029] Other examples include 4,4'-dialkylaminobenzophenones such as 4,4'-bis-(dimethylamino)benzophenone and 4,4'-bis-(diethylamino)benzophenone, and benzophenone compounds such as 4-benzoyl-4'-methyldiphenyl sulfide.
[0030] Other examples include benzophenone, 4-methyl-benzophenone, 2,4,6-trimethylbenzophenone, 2,3,4-trimethylbenzophenone, 4-phenylbenzophenone, 3,3'-dimethyl-4-methoxybenzophenone, 4-(1,3-acryloyl-1,4,7,10,13-pentaoxotridecyl)benzophenone, methyl-o-benzoylbenzoate, [4-(methylphenylthio)phenyl]phenylmethanone, diethoxyacetophenone, dibutoxyacetophenone, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and benzoin normal butyl ether.
[0031] In the present invention, the general-purpose photopolymerization initiators may be used alone or in combination of several kinds.
[0032] [Sensitizers / Photoinitiator assistants] In the present invention, in addition to the general-purpose photopolymerization initiator, a photosensitizer or a photoinitiator assistant such as a tertiary amine may be used in combination, and is preferred. The photosensitizer is not particularly limited, but examples thereof include thioxanthone-based, benzophenone-based such as 4,4'-bis(diethylamino)benzophenone, anthraquinone-based, and coumarin-based.
[0033] When a sensitizer or photoinitiator is used in combination, the amount is preferably 0.05 to 10% by mass, more preferably 0.1 to 7.0% by mass, based on the total solid content of the ink. If the amount is less than 0.05% by mass, sufficient improvement in curability cannot be obtained, and if the amount is more than 10% by mass, the hue of the cured coating film may become unacceptably yellowish, the sensitizer may precipitate, or the fluidity of the ink may decrease significantly.
[0034] On the other hand, examples of tertiary amines include, but are not limited to, ethyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, N,N-dimethylbenzylamine, N,N-dimethylaniline, N,N-diethylaniline, N,N-dimethyl-p-toluidine, N,N-dihydroxyethylaniline, triethylamine, and N,N-dimethylhexylamine, 2-ethylhexyl-4-(dimethylamino)benzoate, 2-butoxyethyl-4-(dimethylamino)benzoate, and the like. These amines reduce polymerization inhibition caused by oxygen, react with thioxanthones and 4,4'-dialkylaminobenzophenones activated by ultraviolet light, become active radical donors, improve the curing performance of the ink, and improve the solubility of the photopolymerization initiator. The tertiary amine is preferably used in combination within a range that does not impair the printing performance of the active energy ray-curable ink of the present invention, and is preferably used in an amount of 0.1 to 10 mass % relative to the total amount of ink solids, and more preferably 0.1 to 5.0 mass %.
[0035] In addition, in applications where high hygiene is required, high molecular weight compounds in which multiple photosensitizers or tertiary amines are branched with polyhydric alcohols or the like within one molecule can also be used as appropriate.
[0036] (Photocatalyst) The photocatalyst used in the present invention is a photocatalyst containing titanium oxide including crystalline rutile titanium oxide and a divalent copper compound, wherein the crystalline rutile titanium oxide is a titanium oxide having a full width at half maximum of the strongest diffraction peak corresponding to rutile titanium oxide of 0.65 degrees or less in an X-ray diffraction pattern obtained by plotting diffraction line intensity against the diffraction angle 2θ using Cu-Kα radiation, and the content of the crystalline rutile titanium oxide in the titanium oxide is 50 mol % or more and the content of anatase titanium oxide is less than 50 mol %.
[0037] By combining rutile-type titanium oxide, which is highly crystalline, with a divalent copper compound, it is possible to obtain a photocatalyst (a visible light responsive photocatalyst having photocatalytic activity such as antiviral activity in the visible light region) that is excellent in antiviral properties in both bright and dark places and in decomposing organic compounds in bright places. In addition, since divalent copper compounds are less likely to discolor due to oxidation, unlike monovalent copper compounds, discoloration over time can also be suppressed.
[0038] In the present invention, the term "bright place" refers to a place where visible light is present, and the term "dark place" refers to a place where no light is present.
[0039] Here, photocatalytic activity means at least one selected from photoinduced decomposition and photoinduced hydrophilization. Photoinduced decomposition is the action of oxidatively decomposing organic matter adsorbed on the surface treated with titanium oxide, and photoinduced hydrophilization is the action of making the surface treated with titanium oxide hydrophilic and compatible with water. This photoinduced hydrophilization is thought to occur when holes generated by photoexcitation and diffused increase the number of hydroxyl groups on the titanium oxide surface.
[0040] In addition, the term "virus" refers to DNA viruses and RNA viruses, but also includes bacteriophages (hereinafter sometimes abbreviated as "phages"), which are viruses that infect bacteria.
[0041] Next, each component of the photocatalyst will be described. (Titanium dioxide) The titanium oxide used in the photocatalyst contains crystalline rutile-type titanium oxide.
[0042] In the present invention, crystalline rutile titanium oxide means titanium oxide in which the full width at half maximum of the strongest diffraction peak corresponding to rutile titanium oxide is 0.65 degrees or less in an X-ray diffraction pattern obtained by plotting the diffraction line intensity against the diffraction angle 2θ using Cu-Kα radiation.
[0043] If the full width at half maximum is greater than 0.65 degrees, the crystallinity is poor and antiviral properties in a dark place are not sufficiently expressed. From this viewpoint, the full width at half maximum is preferably 0.6 degrees or less, more preferably 0.5 degrees or less, even more preferably 0.4 degrees or less, and still more preferably 0.35 degrees.
[0044] The content of crystalline rutile titanium oxide in titanium oxide (hereinafter sometimes referred to as "rutile ratio") is 50 mol% or more. When the content is 50 mol% or more, the obtained photocatalyst has sufficient antiviral properties in a bright place and in a dark place, and also has sufficient organic compound decomposition properties in a bright place and, in particular, visible light responsiveness. From this viewpoint, the rutile ratio is preferably 90 mol% or more, and more preferably 94 mol% or more. This rutile ratio is a value measured by XRD, as described later.
[0045] From the above viewpoints, the content of anatase type titanium oxide in titanium oxide (hereinafter sometimes referred to as "anatase ratio") is preferably small, and the anatase ratio is less than 50 mol%, preferably less than 10 mol%, more preferably less than 7 mol%, and even more preferably 0 mol% (i.e., no anatase type titanium oxide is contained). Like the rutile ratio, this anatase ratio is a value measured by XRD.
[0046] The specific surface area of titanium oxide is preferably 1 to 200 m2 / g. When the specific surface area is 1 m2 / g or more, the frequency of contact with viruses, bacteria, and organic compounds increases due to the large specific surface area, and the obtained photocatalyst has excellent antiviral properties in light and dark places, organic compound decomposition properties, and antibacterial properties. On the other hand, when the specific surface area is 200 m2 / g or less, the handling properties are excellent. From these viewpoints, the specific surface area of titanium oxide is more preferably 3 to 100 m2 / g, further preferably 4 to 70 m2 / g, and particularly preferably 8 to 50 m2 / g. Here, the specific surface area is a value measured by the BET method using nitrogen adsorption.
[0047] Titanium oxide can be produced by either a gas phase method or a liquid phase method, and either can be used, but titanium oxide produced by a gas phase method is more preferable.
[0048] The gas phase method is a method of obtaining titanium oxide by gas phase reaction with oxygen using titanium tetrachloride as a raw material. The titanium oxide obtained by the gas phase method has a uniform particle size and is highly crystalline because it is produced through a high-temperature process. As a result, the obtained photocatalyst has good antiviral properties in both bright and dark places, organic compound decomposition properties, and antibacterial properties.
[0049] On the other hand, the liquid phase method is a method of obtaining titanium oxide by hydrolyzing or neutralizing a liquid in which titanium oxide raw materials such as titanium chloride and titanyl sulfate are dissolved. Titanium oxide produced by the liquid phase method tends to have low rutile crystallinity and a large specific surface area. In this case, it is possible to obtain titanium oxide with optimal crystallinity and specific surface area by carrying out calcination or the like, but since this is time-consuming, the gas phase method is more suitable.
[0050] As for titanium oxide, it is advantageous to use commercially available titanium oxide as it is, in view of the catalyst preparation process.
[0051] (divalent copper compound) The photocatalyst contains a divalent copper compound. This divalent copper compound alone does not have antiviral properties in light and dark places, organic compound decomposition properties in light, or visible light responsiveness, but by combining it with the above-mentioned crystalline rutile titanium oxide, the antiviral properties in light and dark places, organic compound decomposition properties in light, and visible light responsiveness are fully expressed. In addition, this divalent copper compound is less susceptible to discoloration due to oxidation, etc., compared to monovalent copper compounds, so that photocatalysts using this divalent copper compound are less susceptible to discoloration.
[0052] The divalent copper compound is not particularly limited, and may be one or two of an inorganic divalent copper compound and an organic divalent copper compound.
[0053] Examples of the divalent copper inorganic compound include one or more selected from the group consisting of copper sulfate, copper nitrate, copper iodate, copper perchlorate, copper oxalate, copper tetraborate, ammonium copper sulfate, copper amidosulfate, and ammonium copper chloride, copper pyrophosphate, inorganic acid salts of divalent copper consisting of copper carbonate, divalent copper halides consisting of copper chloride, copper fluoride, and copper bromide, as well as copper oxide, copper sulfide, azurite, malachite, and copper azide.
[0054] Examples of divalent copper organic compounds include divalent copper carboxylates. Examples of divalent copper carboxylates include copper formate, copper acetate, copper propionate, copper butyrate, copper valerate, copper caproate, copper enanthate, copper caprylate, copper pelargonate, copper caprate, copper myristic acid, copper palmitate, copper margarate, copper stearate, copper oleate, copper lactate, copper malate, copper citrate, copper benzoate, copper phthalate, copper isophthalate, copper terephthalate, copper salicylate, copper mellitic acid, copper oxalate, and copper malonate. Examples of the divalent copper organic compound include one or more selected from the group consisting of copper oxine, copper acetylacetone, copper ethylacetoacetate, copper isovalerate, copper β-resorcylate, copper diacetoacetate, copper formylsuccinate, copper salicylamine, copper bis(2-ethylhexanoate), copper sebacate, and copper naphthenate. Examples of the divalent copper organic compound include one or more selected from the group consisting of copper oxine, copper acetylacetone, copper ethylacetoacetate, copper trifluoromethanesulfonate, copper phthalocyanine, copper ethoxide, copper isopropoxide, copper methoxide, and copper dimethyldithiocarbamate.
[0055] Of the divalent copper compounds, preferred are one or more of copper oxide, divalent copper halides, inorganic acid salts of divalent copper, and carboxylates of divalent copper, for example, one or more of divalent copper halides, inorganic acid salts of divalent copper, and carboxylates of divalent copper.
[0056] Moreover, the divalent copper compound may be a divalent copper compound represented by the following general formula (1). Cu2(OH)3X (1) In general formula (1), X is an anion, preferably a halogen such as Cl, Br, or I, a conjugate base of a carboxylic acid such as CH3COO, a conjugate base of an inorganic acid such as NO3 or (SO4)1 / 2, or OH.
[0057] Among these divalent copper compounds, divalent copper inorganic compounds are more preferable from the viewpoint of economical efficiency and containing less impurities, and copper oxide is even more preferable. Also preferred is a divalent copper compound represented by the above general formula (1). The divalent copper compound may be an anhydride or a hydrate.
[0058] The copper-equivalent content of the divalent copper compound is preferably 0.01 to 20 parts by mass relative to 100 parts by mass of the titanium oxide. When it is 0.01 part by mass or more, the antiviral properties, organic compound decomposition properties, and antibacterial properties in both light and dark places are good. When it is 20 parts by mass or less, the titanium oxide surface is prevented from being covered, and the photocatalytic functions (organic compound decomposition properties, antibacterial properties, etc.) are well exhibited, and the antiviral performance can be improved with a small amount, which is economical. From this viewpoint, the copper-equivalent content of the divalent copper compound is more preferably 0.1 to 20 parts by mass, even more preferably 0.1 to 15 parts by mass, and even more preferably 0.3 to 10 parts by mass relative to 100 parts by mass of the titanium oxide.
[0059] Here, the copper content of the divalent copper compound per 100 parts by mass of titanium oxide can be calculated from the amounts of the raw materials of the divalent copper compound and the raw materials of titanium oxide charged. The copper content can also be determined by measuring the photocatalyst by ICP (inductively coupled plasma) emission spectrometry, which will be described later.
[0060] As described above, the photocatalyst contains titanium oxide including crystalline rutile-type titanium oxide and a divalent copper compound as essential components, but may contain other optional components within the scope that does not impair the object of the present invention. However, from the viewpoint of improving the function as a photocatalyst and antiviral performance, the content of the essential components in the photocatalyst is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 99% by mass or more, and even more preferably 100% by mass.
[0061] The photocatalyst can be produced by carrying out a mixing step of mixing titanium oxide including crystalline rutile-type titanium oxide with a divalent copper compound raw material. The mixture obtained by this mixing step may be further subjected to a heat treatment step to obtain the photocatalyst. The photocatalyst can also be obtained by suspending titanium oxide in an aqueous solution of a copper compound and allowing it to adsorb. Specifically, the photocatalyst can be produced by the method described in Japanese Patent No. 5343176.
[0062] It is preferable that the primary particle size of the photocatalyst is in the range of about 200 to 400 nm and the secondary particle size is about 3 to 10 μm, since the photocatalyst can be dispersed in a coating agent and has excellent photocatalytic activity such as antiviral properties. The primary particle size was measured using a transmission electron microscope (TEM) by directly measuring the size of the primary particles from electron microscope photographs.
[0063] In order to express photocatalytic activity such as antiviral activity without impairing various properties such as transparency, curability, printability, and gloss of the overprint varnish, the photocatalyst is preferably contained in the range of 0.05% by mass or more and 15% by mass or less based on the total solid content of the coating agent for paper substrates or plastic substrates of the present invention. Furthermore, when high transparency is required for the overprint varnish, it is preferable to contain the photocatalyst in the range of 0.05% by mass or more and 5% by mass or less, and more preferably 0.05% by mass or more and 2% by mass or less. If the amount is less than 0.05% by mass, the desired antiviral and antibacterial properties cannot be obtained, while if the amount is more than 15% by mass, the image at the bottom of the varnish becomes unclear, significantly impairing the aesthetic appearance. In addition, titanium oxide significantly reflects ultraviolet light irradiated from an ultraviolet irradiator, so that the curing performance is significantly reduced. Furthermore, due to the effect of an increase in titanium oxide particles with a high specific gravity in the overprint varnish, the inherent rheological properties of the overprint varnish are significantly disrupted, and offset printing suitability is deteriorated.
[0064] The method of mixing the photocatalyst used in the present invention with the active energy ray-curable overprint varnish can be produced by mixing a powdered photopolymerization initiator, extender pigment and the photocatalyst in a liquid composed of the monomer, oligomer, resin solution, various additives and the like used in the overprint varnish, pre-dispersing the mixture with a known, publicly used dispersion stirrer, and then grinding and dispersing the mixture until a particle size suitable for offset printing is obtained using a milling disperser such as a three-roll mill or a bead mill. Alternatively, the photocatalyst can be blended at a high concentration with a binder component composed of a monomer, oligomer and resin solution, and milled until a particle size suitable for offset printing is obtained to produce a high-concentration photocatalyst base, and the high-concentration photocatalyst base can be blended at a desired concentration into an overprint varnish that does not contain a photocatalyst that has been produced in a separate process, and mixed with a known, publicly used dispersion stirrer to produce an active energy ray-curable overprint varnish containing a photocatalyst.
[0065] (Other additives) Examples of other additives that impart abrasion resistance, anti-blocking properties, smoothness, and anti-scratch properties include natural waxes such as carnauba wax, Japan wax, lanolin, montan wax, paraffin wax, and microcrystalline wax, and synthetic waxes such as Fischer-Tropsch wax, polyethylene wax, polypropylene wax, polytetrafluoroethylene wax, polyamide wax, and silicone compounds.
[0066] Further, examples of additives that impart storage stability to the ink include polymerization inhibitors such as (alkyl)phenols, hydroquinone, catechol, resorcin, p-methoxyphenol, t-butylcatechol, t-butylhydroquinone, pyrogallol, 1,1-picrylhydrazyl, phenothiazine, p-benzoquinone, nitrosobenzene, 2,5-di-tert-butyl-p-benzoquinone, dithiobenzoyl disulfide, picric acid, cupferron, aluminum N-nitrosophenylhydroxylamine, tri-p-nitrophenylmethyl, N-(3-oxyanilino-1,3-dimethylbutylidene)aniline oxide, dibutyl cresol, cyclohexanone oxime cresol, guaiacol, o-isopropylphenol, butyraldoxime, methyl ethyl ketoxime, and cyclohexanone oxime.
[0067] In addition, additives such as ultraviolet absorbers, infrared absorbers, and antibacterial agents can be added depending on the required performance.
[0068] The active energy ray curable overprint varnish of the present invention can be used without a solvent, or can be used with an appropriate solvent as necessary. The solvent is not particularly limited as long as it does not react with the above-mentioned components, and can be used alone or in combination of two or more kinds.
[0069] The active energy ray-curable overprint varnish of the present invention may be produced by a method similar to that of the conventional method, for example, by mixing raw materials such as the resin, acrylic monomer or oligomer, polymerization inhibitor, initiator, sensitizer such as an amine compound, photocatalyst used in the present invention and other additives at a temperature between room temperature and 100°C using a milling, mixing and adjustment machine such as a kneader, three-roll mill, attritor, sand mill or gate mixer.
[0070] (Printed material) The printed matter of the present invention is obtained by applying the above-mentioned overprint varnish composition directly onto a substrate or onto a printed matter printed by a lithographic offset printing machine using the printing ink composition. The overprint varnish composition may be applied to the entire surface of the printed matter, or may be applied only to a part of the printed matter. The amount of application may be appropriately adjusted depending on the purpose of applying the overprint varnish composition, and as an example, the amount of application is adjusted so that the coating film of the overprint varnish composition after drying has a thickness of about 0.5 μm to 1.5 μm.
[0071] The coating method may be a so-called in-line method in which a coating device is incorporated into a lithographic offset printing machine and the overprint varnish composition is applied following printing using the printing ink composition, or a so-called offline method in which coating is performed using a coater machine equipped with a gravure or flexographic coating device after printing using the lithographic offset printing machine.
[0072] (Paper base material) The substrate is not particularly limited and may be one that is conventionally known, but is particularly suitable for printing on paper substrates such as coated paper, matte coated paper, fine paper, etc. Also usable are backing paper, impregnated paper, cardboard, and paperboard.
[0073] (Plastic substrate) It may also be applied to a plastic substrate. The plastic substrate may be any substrate used for plastic materials, molded products, film substrates, packaging materials, etc. Specific examples include polyamide resins such as nylon 6, nylon 66, and nylon 46; polyester-based resins such as polyethylene terephthalate (hereinafter sometimes referred to as PET), polyethylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polybutylene terephthalate, and polybutylene naphthalate; biodegradable resins such as polyhydroxycarboxylic acids such as polylactic acid, aliphatic polyester-based resins such as poly(ethylene succinate) and poly(butylene succinate); polyolefin resins such as polypropylene and polyethylene, polyimide resins, polyarylate resins, and mixtures thereof; and films and laminates thereof made of thermoplastic resins, among which films made of polyethylene terephthalate (PET), polyester, polyamide, polyethylene, and polypropylene can be preferably used. These substrate films may be unstretched or stretched films, and the manufacturing method is not limited. The thickness of the substrate film is not particularly limited, but is usually within the range of 1 to 500 μm. The substrate film is preferably subjected to a corona discharge treatment, and may be vapor-deposited with aluminum, silica, alumina, etc. The substrate may be a laminate (sometimes called a laminate film) having a laminate structure in which the above-mentioned paper substrate or film substrate is laminated by a dry lamination method, a solventless lamination method, or an extrusion lamination method.
[0074] The paper substrate or plastic substrate may further have a printing ink layer. The printing ink used for the printing ink layer is not particularly limited, and it is possible to coat the printing layer with an offset lithographic ink, a gravure printing ink, a flexographic printing ink, an inkjet printing ink, or the like. In particular, as described above, a method of coating a printed matter printed by a lithographic offset printing machine using an offset printing ink composition is industrially preferred.
[0075] (containers, packaging materials) The single-layer paper or film substrate, and laminates having a laminated structure are variously expressed, depending on the industry, the method of use, etc., as functional films, soft packaging films, shrink films, films for packaging daily necessities, films for packaging medicines, films for packaging food, cartons, posters, flyers, CD jackets, direct mail, pamphlets, fine paper, coated paper, art paper, imitation paper, thin paper, cardboard, and various synthetic papers used for packaging cosmetics, beverages, medicines, toys, equipment, etc., but the overprint varnish of the present invention can be used without any particular limitation. Furthermore, these substrates after coating with the overprint varnish of the present invention are formed into containers or packaging materials, and in this case, it is preferable that the overprint varnish of the present invention is coated on the surface that will become the outermost layer when the container or packaging material is made using these.
[0076] The contents and effects of the present invention will be explained in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0077] <Preparation of photocatalyst> First, the properties of the titanium oxide raw material (manufactured by Showa Denko Ceramics K.K.) used were measured as follows.
[0078] (BET specific surface area) The BET specific surface area of the titanium oxide raw material was measured using a fully automatic BET specific surface area measuring device "Macsorb, HM model-1208" manufactured by Mountec Co., Ltd. (Rutile content (rutile ratio) and crystallinity (full width at half maximum) in titanium oxide raw material) The content of rutile-type titanium oxide in the titanium oxide raw material (rutilated ratio) and the crystallinity (full width at half maximum) were measured by powder X-ray diffraction.
[0079] That is, X-ray diffraction measurements were performed on the dried titanium oxide raw material using a PANalytical "X'pertPRO" measurement device, a copper target, and Cu-Kα1 radiation under conditions of a tube voltage of 45 kV, a tube current of 40 mA, a measurement range of 2θ = 20 to 100 deg, a sampling width of 0.0167 deg, and a scanning speed of 3.3 deg / min.
[0080] The peak height (Hr) corresponding to rutile crystals, the peak height (Hb) corresponding to brookite crystals, and the peak height (Ha) corresponding to anatase crystals were determined, and the content of rutile titanium oxide in titanium oxide (rutile ratio) was calculated using the following formula.
[0081] Rutile ratio (mol%) = {Hr / (Ha+Hb+Hr)} x 100 Further, the content of anatase type titanium oxide (anatase ratio) and the content of brookite type titanium oxide (brookite ratio) in the titanium oxide were calculated by the following formulas.
[0082] Anatase rate (mol%) = {Ha / (Ha+Hb+Hr)} x 100 Brookite conversion rate (mol%) = {Hb / (Ha+Hb+Hr)} x 100 In the X-ray diffraction pattern obtained by the above X-ray diffraction measurement, the most intense diffraction peak corresponding to rutile-type titanium oxide was selected, and the full width at half maximum was measured.
[0083] (Primary particle size) The average primary particle diameter (DBET) (nm) was calculated by measuring the specific surface area S (m2 / g) of titanium dioxide using the BET single point method and calculating the following formula: DBET = 6000 / (S × ρ) Here, ρ is the density of titanium oxide (g / cm3).
[0084] The measurement results of the titanium oxide raw material used are shown in Table 1.
[0085] [Table 1]
[0086] (Production Example 1) 6 g (100 parts by mass) of titanium oxide raw material (manufactured by Showa Denko Ceramics Co., Ltd.) was suspended in 100 mL of distilled water, and 0.0805 g (0.5 parts by mass in terms of copper) of CuCl2·2H2O (manufactured by Kanto Chemical Co., Ltd.) was added and stirred for 10 minutes. A 1 mol / L aqueous solution of sodium hydroxide (manufactured by Kanto Chemical Co., Ltd.) was added so that the pH became 10, and the mixture was stirred and mixed for 30 minutes to obtain a slurry. This slurry was filtered, and the obtained powder was washed with pure water, dried at 80°C, and crushed in a mixer to obtain a sample (photocatalyst).
[0087] The obtained sample (photocatalyst) was heated in a hydrofluoric acid solution until it was completely dissolved, and the extract was quantified by ICP atomic emission spectrometry. The result was that the amount of copper ions was 0.5 parts by mass per 100 parts by mass of titanium oxide. In other words, the entire amount of copper ions (derived from CuCl2·2H2O) that had been added was supported on the titanium oxide surface.
[0088] The sample (photocatalyst) obtained in Production Example 1 was analyzed by the following method.
[0089] (Rutile titanium dioxide content (rutile ratio) and crystallinity (full width at half maximum)) For the sample (photocatalyst) obtained in Production Example 1, the content of rutile-type titanium oxide in titanium oxide (rutilated ratio) and the crystallinity (full width at half maximum) were measured by powder X-ray diffraction method.
[0090] That is, the dried photocatalyst was ground in a mortar to prepare a powder sample. X-ray diffraction measurements were performed on this sample using a PANalytical X'pertPRO measuring device, a copper target, and Cu-Kα1 radiation under the following conditions: tube voltage 45 kV, tube current 40 mA, measurement range 2θ = 20 to 100 deg, sampling width 0.0167 deg, and scanning speed 3.3 deg / min.
[0091] The peak height (Hr) corresponding to rutile crystals, the peak height (Hb) corresponding to brookite crystals, and the peak height (Ha) corresponding to anatase crystals were determined, and the content of rutile titanium oxide in titanium oxide (rutile ratio) was calculated using the following formula.
[0092] Rutile ratio (mol%) = {Hr / (Ha+Hb+Hr)} x 100 In the X-ray diffraction pattern obtained by the above X-ray diffraction measurement, the most intense diffraction peak corresponding to rutile-type titanium oxide was selected, and the full width at half maximum was measured.
[0093] (Identification of divalent copper compounds) The divalent copper compound present in the sample (photocatalyst) obtained in Production Example 1 was identified by X-ray diffraction measurement using the above-mentioned measuring device and measuring conditions. The results are shown in Table 2.
[0094] [Table 2]
[0095] [Production of diallyl phthalate resin solution] In a metal container, 67.6% by mass of Miramer M-600 manufactured by MIWON was placed and heated to 80° C. while stirring. After the temperature reached 80° C., 32.4% by mass of DAISO DAP-A, which had been crushed in advance, was gradually added while stirring. After the resin was added, the temperature was raised to 110° C. while blowing in air, and stirring was continued for 1 hour in that state to completely dissolve the resin. In Table 1, the decomposed composition is shown in order to clarify the blending amount of the diallyl phthalate resin.
[0096] [Production of active energy ray overprint varnish] Various ink compositions were obtained by milling the inks of Examples 1 to 8 and Comparative Examples 1 and 2 in a three-roll mill according to the compositions in Table 3. Note that blanks in the table indicate that no ink was added.
[0097] [Antibacterial property evaluation method] Using a simple color spreader (RI Tester, manufactured by Toyoei Seiko Co., Ltd.), 0.10 ml of the inks prepared above in Examples 1 to 8 and Comparative Examples 1 and 2 was spread evenly on the rubber roll and metal roll of the RI Tester, and applied to a PET roll (Toray Lumirror Film T60 #250) to a thickness of about 220 cm. 2 The coated material was applied so as to be uniformly coated over the entire area. A UV irradiation device (manufactured by iGraphics) equipped with a water-cooled UV-LED (central emission wavelength 385 nm ± 5 nm UV-LED output 100%) and a belt conveyor was used to place the coated material on the conveyor and pass it directly under the LED (irradiation distance 9 cm) at a conveyor speed of 100 m / min. The coated material after the photocurable ink coating obtained by the above method was irradiated with ultraviolet (UV) light to cure and dry the ink film. A bacterial solution was dropped onto the coated surface of the cured overprint varnish obtained above, and the viable bacterial count was measured after 24 hours at 35°C and 90% humidity. If the number of bacteria was less than 1 / 1000 of the inoculated number, it was marked as ○, if it was less than 1 / 100, it was marked as △, and otherwise it was marked as ×. Two types of bacteria were evaluated: Staphylococcus aureus and Escherichia coli.
[0098] [Method for evaluating antiviral activity] Cured products of the active energy ray overprint varnishes described in Examples 1 to 8 and Comparative Examples 1 and 2 were prepared using the method described above for evaluating antibacterial properties. Thereafter, a virus liquid was dropped onto the coated surface of the cured overprint varnish, and the virus count was measured after 24 hours at 25°C. If the number of inoculated viruses was less than 1 / 1000, it was marked with an ◯; if it was less than 1 / 100, it was marked with a △; otherwise it was marked with an ×. Two types of viruses were evaluated: influenza A virus and feline calicivirus.
[0099] [How to check suitability for offset printing] In order to control the print film thickness by color density, 95% by mass of the ink having the composition described in Examples 1 to 8 and Comparative Examples 1 and 2 was mixed with 5% by mass of DC HRL SP-LK2 Indigo S manufactured by DIC Graphics in a three-roll mill, and toned with indigo blue. The UV irradiation device used was a Lithrone G40 manufactured by Komori Corporation, equipped with a water-cooled metal halide lamp (output 160W / cm, 3 lamps used) manufactured by Eye Graphics. Offset printing was carried out at a printing speed of 10,000 sheets per hour. The printing paper used was Oji Paper OK Topcoat Plus (57.5 kg, A size). The dampening water supplied to the plate surface was an aqueous solution made by mixing 97.5% by weight of tap water and 2.5% by weight of an etching solution (Presert SU, manufactured by DIC Graphics). Next, the ink supply key was operated so that the indigo density of the solid area was 0.25 (measured with a SpectroEye densitometer manufactured by X-Rite), and when the density stabilized, the ink supply key was fixed. The coating amount of each ink composition at the above indigo concentration was measured to be 1 g / m2. After printing 3,000 sheets under the above conditions, the degree of emulsified ink accumulation in the non-feeding areas of the offset printing press was checked according to the following criteria to evaluate the offset printing suitability. No emulsified ink was found on the entire non-feeding portion of the impression cylinder. △Emulsified ink adhesion was observed on less than 50% of the area of the non-feeding part of the impression cylinder. ×: Emulsified ink adhesion was observed on 50% or more of the area of the non-feeding part of the impression cylinder.
[0100] [Curing property evaluation method] The curability was evaluated by using the 3000th print produced by offset printing using the above method, and the surface of a solid portion of the print was scratched with a fingernail using the fingernail scratch method in the following manner. ◯: No scratches were observed when scratched with a fingernail, and the curing property was excellent. △: Scratches caused by fingernails are visible, but still usable. ×: Scratches easily caused by fingernail scratching, and curing properties were the worst.
[0101] How to measure [60° gloss] The gloss was evaluated using the 3000th print produced by offset printing using the above method, using a Konica Minolta GM-268plus, according to the following criteria. ○: 30 or more △: 25 to less than 30 ×: Less than 25
[0102] The compositions and evaluation results of the active energy ray-curable overprint varnishes of the present invention are shown in Tables 3 and 4. Note that blank spaces indicate that no ingredients were used. Details of the raw materials shown in Tables 3 and 4 are shown in Table 5.
[0103] [Table 3]
[0104] [Table 4]
[0105] [Table 5]
[0106] From the above results, it is clear that the active energy ray-curable overprint varnishes of the Examples have excellent antibacterial and antiviral activities.
Claims
1. An active energy ray-curable overprint varnish containing an active energy ray-curable compound as a main component, the active energy ray-curable overprint varnish contains a photocatalyst, the photocatalyst contains titanium oxide including crystalline rutile titanium oxide and a divalent copper compound, the crystalline rutile titanium oxide is a titanium oxide having a full width at half maximum of 0.65 degrees or less of the strongest diffraction peak corresponding to rutile titanium oxide in an X-ray diffraction pattern obtained by plotting diffraction line intensity against the diffraction angle 2θ using Cu-Kα radiation, the content of the crystalline rutile titanium oxide in the titanium oxide is 50 mol % or more and the content of anatase titanium oxide is less than 50 mol %, and the photocatalyst is contained in an amount of 0.05 to 15 mass % based on the total amount of solids in the varnish, The active energy ray-curable overprint varnish comprises a polyester (meth)acrylate having a glass transition temperature of 250°C or higher and a diallyl phthalate resin having a glass transition temperature of 140 to 160°C, and the total mass of the polyester acrylate having a glass transition temperature of 250°C or higher and the diallyl phthalate resin having a glass transition temperature of 140 to 160°C is 10 to 70 mass% based on the total amount of the active energy ray-curable overprint varnish.
2. 2. The active energy ray-curable overprint varnish according to claim 1, which contains an alkylphenone-based photopolymerization initiator as the photopolymerization initiator.
3. A printed matter comprising a substrate and a coating of the active energy ray-curable overprint varnish according to claim 1 or 2 disposed on the substrate.
4. A paper substrate or a plastic substrate, which is coated with the active energy ray-curable overprint varnish according to claim 1 or 2.
5. The paper or plastic substrate according to claim 4, further comprising a printing ink layer.
6. A container or packaging material using the paper substrate or plastic substrate according to claim 4 or 5.
Citation Information
Patent Citations
Active energy ray-curable composition for overcoating and cured product thereof
JP1995196948A
Hard coat sheet
JP1999057603A
Overprinting varnish composition
JP1999080643A
Photocurable composition for film coating
JP2001247793A
Masking coating and cap coated with the same masking coating
JP2006241290A